The Development of Muslim Society during the Ayyubid Dynasty - Rina Rina; Zulkifli Musthan (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The development of society during the Ayyubid Dynasty marked a significant phase in the history of Islamic civilisation following the decline of the Fatimid Dynasty. Founded by Salahuddin al-Ayyubi, this dynasty is recognised not only for its success in confronting the Crusades but also for its role in establishing a more stable social, economic, and religious order. Objective: This study aims to analyse the dynamics of societal development and the factors influencing it. Method: The research employs a historical method with a qualitative approach, analysing primary and secondary sources, including chronicles, administrative documents, literary works, travel records, and archaeological and numismatic findings. Results: The findings indicate that political stability contributed to stronger governance and the enforcement of law. In the economic sector, the development of agriculture, trade, and craft industries enhanced public welfare. Support for education through madrasas and bimaristans also promoted intellectual growth. Conclusion: This study concludes that the Ayyubid Dynasty succeeded in shaping a stable and productive society. Contribution: This research serves as a scholarly reference for understanding the socio-economic and intellectual development of Muslim societies during the Ayyubid period, and provides a historical foundation for further studies in Islamic civilisation.